AS04 drives superior cross-protective antibody response by increased NOTCH signaling of dendritic cells and proliferation of memory B cells - D’Onofrio, Valentino; Santana, Ana Carolina; Pauwels, Marthe; Waerlop, Gwenn; Willems, Anthony; De Boever, Fien; Müller, Martin; Sehr, Peter; Waterboer, Tim; Leroux-Roels, Isabel; Sharma, Ashish A.; Sékaly, Rafick Pierre; et al. (Frontiers in Immunology, 2025)
IntroductionThe Gardasil-4® vaccine targets HPV types 6, 11, 16 and 18 and is formulated with amorphous alum. Cervarix® targets HPV types 16 and 18 using AS04 (Al(OH)3 + TLR4 agonist MPL) to enhance immune response. Cervarix elicits higher cross-protection against other high-risk HPV types, likely mediated by AS04.MethodsTo investigate mechanisms of cross-neutralizing potential, six monozygotic twins (12 females aged 9-13 years) were vaccinated with either Cervarix or Gardasil-4 (2 doses, 6 months apart). Serum neutralizing antibody titers against HPV 6,16,18,31,33,45,52, and 58 were assessed pre-vaccination and 7 days post-second dose. Multi-omic single cell RNA and ATAC sequencing of PBMCs was performed at the latter timepoint.ResultsCervarix generated higher cross-neutralizing antibody titers than Gardasil-4. Higher frequencies of dendritic cells and memory B cells were observed. Gene Set Enrichment Analysis (GSEA) indicated enhanced pathways related to NOTCH2 signaling in DCs and cell cycling/RNA translation in B cells, correlating positively with cross-neutralizing antibody titers. Increased chromatin accessability in genes related to NOTCH signaling in cDC1 was also observed. Cervarix-vaccinated subjects showed increased DC-to-memory B signaling, through upregulation of NOTCH ligands. Engagement of NOTCH was associated to BCL2 expression in memory B cells, supporting an anti-apoptotic state.ConclusionIncreased DC signaling, including NOTCH, through AS04 in Cervarix supports cell survival and sustained RNA translation in memory B cells, 7 days post-vaccination. This may enhance adaptive immune cell maturation, providing a mechanism that can lead to improved cross-reactivity.